Xylazine-Ketamine Outperforms Diazepam-Ketamine in Rabbit Anesthesia: Xylazine-Ketamin Mengungguli Diazepam-Ketamin dalam Anestesi Kelinci - Mohammed R. Abduljaleel (Academia Open, 2024)
Background: Limited research on the effects of ketamine combinations on rabbit anesthesia underscores the need for safe and effective injectable methods. Specific Background: This study compares the efficacy and safety of two anesthetic combinations—xylazine-ketamine and diazepam-ketamine —in rabbits to address this gap. Knowledge Gap: Ketamine combinations are commonly used in rabbits, but there is limited data on their effects on analgesic properties and anesthesia duration. Aims: The study assesses the onset of righting reflex loss, analgesia duration, recumbency duration, and standing attempts in rabbits treated with XK and DK. Results: Ten healthy rabbits were administered XK (5 mg xylazine and 10 mg ketamine per kg) or DK (1 mg diazepam and 30 mg ketamine per kg) intramuscularly. The study found no significant difference in OLRR between the groups. Only XK produced significant analgesia (OA: 4.5±0.2 min, DA: 45.1±1.9 min), while DK showed no analgesic effect. DR and ATS were significantly shorter in XK (56.1±3.1 min and 7.3±0.7 min) compared to DK (121.1±7.5 min and 25.3±1.2 min). Novelty: The study compares XK and DK in rabbits, finding XK provides superior analgesia and faster recovery times, while DK is ineffective for pain management. Implications: The study indicates that XK is more effective for analgesic procedures, while DK is recommended for painful treatments with additional analgesics. Highlights: XK Provides Analgesia: Only Xylazine-Ketamine offers significant pain relief. Shorter Recovery Time: XK results in quicker recovery compared to DK. DK Needs Supplement: Diazepam-Ketamine requires additional analgesics for pain management. Keywords: Anesthesia, Xylazine-Ketamine, Diazepam-Ketamine, Rabbits, Analgesia